2010
DOI: 10.1097/fpc.0b013e3283395c6a
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in xenobiotic metabolizing enzymes and diet influence colorectal adenoma risk

Abstract: We report the novel associations between P450 genotype and CRA risk, and highlight the risk association with GSTM1 genotype, common to our CRA and cancer case-control series. In addition, we report a novel modifying influence of GSTP1 genotype on dietary chemoprevention. These novel findings require independent confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 65 publications
3
38
0
Order By: Relevance
“…However, the WCRF/AICR report did not find a significant association between red or processed meat intake and colorectal adenomas, but the number of studies assessed was modest (a total of 5 prospective studies, 4 case-control studies) (5). A number of additional case-control (10)(11)(12)(13)(14)(15)(16) and prospective studies (17)(18)(19)(20)(21)(22) have since been published on the subject. We update the evidence as accumulated up to December 2011 and explore whether the associations reported differed by study design and other study characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the WCRF/AICR report did not find a significant association between red or processed meat intake and colorectal adenomas, but the number of studies assessed was modest (a total of 5 prospective studies, 4 case-control studies) (5). A number of additional case-control (10)(11)(12)(13)(14)(15)(16) and prospective studies (17)(18)(19)(20)(21)(22) have since been published on the subject. We update the evidence as accumulated up to December 2011 and explore whether the associations reported differed by study design and other study characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In further examination of gene-diet interactions, the authors found some evidence of an interaction between the GSTP1 Ala114Val polymorphism and fruit consumption on colorectal adenoma risk (interaction p = 0.02). Fruit consumption was not protective among carriers of the GSTP1 variant allele (OR: 1.28, 95% CI: 0.58–2.83), while it was shown to be protective among those homozygous for the reference allele (OR: 0.49, 95% CI: 0.34–0.71) [61]. Polymorphisms in the GST enzymes have been hypothesized and shown to have both a beneficial and adverse impact on cancer risk, possibly due to the role of GST in eliminating harmful oxidative species and carcinogens as well as beneficial dietary chemoprotective chemicals such as isothiocyanates found in cruciferous vegetables (fig.…”
Section: Glutathione S-transferasesmentioning
confidence: 99%
“…23,60]. For example, a recent study examined 19 polymorphisms in 13 genes coding xenobiotic metabolizing enzymes including GSTM1 , GSTT1 , and GSTP1 in 308 premalignant adenoma cases identified by colonoscopy and 296 controls [61]. Fiber, energy, total vegetable consumption and cruciferous vegetable consumption were all found to be inversely related to colorectal adenoma risk, whereas there was only a modest suggestion of an inverse relationship with fruit consumption and no relationship was found with consumption of red meat.…”
Section: Glutathione S-transferasesmentioning
confidence: 99%
“…The ability to multiplex RT -PCR methods has been described in the literature (Vansant et al, 2006 ;Northwood et al, 2010 ), and the process utilizes slightly different techniques. Additionally, a multiplexed method based on bDNA has also been developed and described in the literature (Flagella et al, 2006 ).…”
Section: Rna Quantifi Cationmentioning
confidence: 99%